Testing the Regional Performance of Multinational Enterprises in the Retail Sector: The Moderating Effects of Timing, Speed and Experience. (9th May 2013) - Mohr, Alex; Fastoso, Fernando; Wang, Chengang; Shirodkar, Vikrant
Abstract : Drawing on regional strategy theory we complement the core effect of firm‐specific advantages on the performance of multinational enterprises with an analysis of the performance consequences of home region concentration on firm performance. We also develop hypotheses regarding the effect of foreign entry timing, internationalization speed and international experience on the performance effect of home region concentration. We test our hypotheses against unique longitudinal data from a panel of 128 multinational enterprises in the retail sector whose geographical spread of international activities we traced between 1995 and 2010. Our findings support the predictions of regional strategy theory and highlight the importance of foreign entry timing and internationalization speed in strengthening the positive effect of home region concentration on the performance of multinational enterprises.